Analysis of The Effectiveness of Online Religious Propagation and Community-Based Religious Activities in Enhancing Religious Knowledge in The Digital Era - Azhar, Muhammad Zul; Nursikin, Mukh; Ahmad, Khatib Ramli (Literasi: Jurnal Ilmu Pendidikan, 2024)
This study aims to investigate the effect of online da'wah and community-based religious activities on increasing religious knowledge in the digital era, with the research subjects involving 34 community members. The research instrument used was a questionnaire with 5 indicators for each research variable. Hypothesis testing was conducted through multiple linear regression tests. The results of statistical analysis showed a t-test value of 1.861 with a significance value (Sig.) of 0.073 for the effect of online da'wah on increasing religious knowledge in the digital era. In addition, the F value of 23.312 with a Sig. 0.000 shows that together, online da'wah and community-based religious activities have a significant influence on increasing religious knowledge in the digital era. Thus, it can be concluded that the combination of online da'wah and community-based religious activities has a significant impact on increasing religious knowledge in the digital era in the research community.